Analisis Pengendalian Kualitas Gulungan Benang Polyester 20s pada Mesin Winding dengan Metode Statistical Quality Control (SQC) Melalui Pendekatan Failure Mode And Effect Analysis (FMEA) di PT. Primayudha Mandirijaya - taufik, taufik; Nurrokhman, Agus; Ilham Wizztyo, Yosanino (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2024)
PT. Primayudha Mandirijaya is a manufacturing company operating in the textile sector. Customer satisfaction is the main goal. Therefore, production quality always comes first. However, there are problems in making this happen, namely that there are often defects in spools of 20s polyester, because these defects greatly exceed the production limit set by the company, namely 5% of total production. The aim of this research is to find out directly the problems that occur in the production process, as well as to find out the resolution of problems that occur on winding machines. To make this happen, the Statistical Quality Control method is used. To determine the possibility of failure, the Failure Mode and Effect Analysis method is used. The results of research using the Statistical Quality Control method, the defect rate of 44.67% in Stitch can be reduced to 43.97% and the defect rate of 36.07% in Swelled Package can be reduced to 29.36%. In the Failure Mode and Effect Analysis method, the factors causing defects are influenced by a lack of attention to components and maintenance on the machine, so the maintenance team is recommended to carry out regular check-ups on the condition of the machine every day. Before repairs were carried out, total defects from January to September reached 68,231.52 or 5.28% of production output. After improvements, the number of defects decreased in October to 6,831.72 or 4.53%. Thus, this research is able to reduce defects in spools of 20s polyester thread by 0.75%. Keywords: Polyester 20S yarn, Statistical Quality Control, Failure Mode and Effect Analysis